An architecture of memory in the work by Gottfried Leibniz from a standpoint of modern investigations - Polyakova, Viktoriya (Actual Problems of Mind, 2017)
The author investigates some aspects of Leibniz’s conception of memory, interconnections between memory and experience and the place of memory in the structure of person. The paper contains an overview of the philosophical heritage of Leibniz as presented in the modern scientiﬁc literature.